THE INFLUENCE OF CONSUMER ENGAGEMENT AND SOCIAL MEDIA MARKETING ON CONSUMER PURCHASE INTENTION OF GAME ITEMS IN MOBILE LEGENDS - Pelealu, Julian Yehezkiel; Worang, Frederik G.; Tielung, Maria V. J. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2025)
This study aims to test the influence of consumer engagement and social media marketing towards purchase intention partially and simultaneously, data were collected through a questionnaire method and because the population are unknown therefore this study uses the Lemeshow formula, rounded up to 100 sample. The data analysis technique used is multiple linear regression analysis which serves to see the effect. The results in this study indicate that both consumer engagement and social media marketing play significant roles in influencing Purchase Intention. When analyzed together (simultaneously), these factors have a combined effect that strongly impacts consumers' intentions to purchase. Separately (partially), each factor also demonstrates a distinct influence on purchase intention. Customer Engagement motivates consumers to interact more actively with the brand, fostering a deeper connection and increasing their likelihood to buy. Meanwhile, Social Media Marketing enhances brand visibility and appeal through strategic campaigns, attracting consumers and encouraging purchase decisions. The combined and individual impacts of these factors emphasize their importance in driving purchase intentions.   Keyword: Consumer Engagement, Social Media Marketing, Purchase Intention